PENGARUH PERTUMBUHAN EKONOMI DAN PERTUMBUHAN PENDUDUK TERHADAP TINGKAT PARTISIPASI ANGKATAN KERJA DI KOTA LHOKSEUMAWE PERIODE 2007-2015 - Putri Susanti; Cut Putri Mellita Sari (JURNAL EKONOMIKA INDONESIA, 2018)
This study aims to determine the effect of economic growth and population growth on labor force participation rate (LFPR) in Lhokseumawe city from 2007 to 2015. The data used in this study is secondary data obtained from the Central Bureau of Statistics (BPS) during 2007 to 2015. Data analysis method used in this research is Multiple Linear regression analysis method with the help of EVIEWS. The results partially (t-test) show that economic growth has a positive and significant effect on labor force participation rate (LFPR) in Lhokseumawe City from 2007 to 2015 and population growth has a positive and significant effect on labor force participation rate (LFPR) in Lhokseumawe City from 2007 to 2015. Simultaneously (F test) indicates that economic growth and population growth have a positive and significant effect on labor force participation rate (LFPR) in Lhokseumawe City from 2007 to 2015. Economic growth and population growth affect labor force participation rate (LFPR) by 14.7863% and the rest 85.2137% is influenced by other variables outside of this study.